1999
DOI: 10.1080/02688699943952
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year clinical follow-up after lumbar disc surgery: results and predictors of outcome

Abstract: This study evaluates the 7-year outcome of lumbar disc surgery and the predictive value of pre- and perioperative risk factors. The 7-year follow-up rate of a sample of 122 patients was 93% (n = 114). Six per cent of the patients had undergone repeat surgery. Approximately 90% reported that they were satisfied with having undergone surgery. The clinical outcome was evaluated in 96 patients (54 men and 42 women) by means of patient-scores (VAS) of low back and leg pain, and a Clinical Overall Score (COS). In mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
3
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 26 publications
2
53
3
3
Order By: Relevance
“…In the present study, 10% of the patients had a permanent work disability pension due to back after 5 years of surgery. Similar but also much differing rates of work disability have been reported earlier [15,22,34,40,49].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the present study, 10% of the patients had a permanent work disability pension due to back after 5 years of surgery. Similar but also much differing rates of work disability have been reported earlier [15,22,34,40,49].…”
Section: Discussionsupporting
confidence: 78%
“…The 2 months sick leave which was routinely prescribed during this study may be inappropriately long in many cases. Longer sick leave has adverse psychosocial impact increasing the odds of permanent loss of employment [6,25] but the rate of work disability here was less than the reported in many studies [15,22,34,40,49]. A 2 months sick leave, however, may cause needless loss of work productivity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Graver et al 42 found that strenuous work activities were related to a lower frequency of return to work. In a subsequent paper, he found that physical fitness has no significant prognostic value 27 , reinforcing the concept that it is not the effort itself, but the patients' perception of it that may influence the outcome for return to work.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a number of studies have suggested that litigation (Bernard, 1993;DeBerard, Masters, Colledge, Schleusener, & Schlegel, 2001;Epker & Block, 2001;Junge, Dvorak, & Ahrens, 1995;LaCaille et al, 2005;Taylor et al, 2000) and insurance compensation or worker's compensation (Bernard, 1993;Deyo, Mirza, Heagerty, Turner, & Martin, 2005;Epker & Block, 2001;Glassman et al, 1998;Greenough, Taylor, & Fraser, 1994;GrothMarnat & Fletcher, 2000;Klekamp, McCarty, & Spengler, 1998;Mannion & Elfering, 2006;Taylor et al, 2000) are also associated with poor surgical outcome. Other identified risk factors for poor surgical outcome include anger (Dvorak, Valach, Fuhrimann, & Heim, 1988;Herron, Turner, & Weiner, 1988), neuroticism , psychological distress (Andersen, Christensen, & Bunger, 2006;Derby et al, 2005;Deyo et al, 2005;Graver, Haaland, Magnaes, & Loeb, 1999; Van Susante, Van de Schaaf, & Pavlov, 1998), psychological trauma in childhood (Schofferman, Anderson, Hines, Smith, & Keane, 1993;Schofferman et al, 1992), chemical dependency (Spengler, Freeman, Westbrook, & Miller, 1980;Uomoto, Turner, & Herron, 1988), spousal reinforcement of pain behaviors , no support from spouse (Schade, Semmer, Main, Hora, & Boos, 1999), self-perception of pre-surgical good health (Katz et al, 1999), fear of movement or reinjury (den Boer, Oostendorp, Beems, Munneke, & Evers, 2006), negative outcome expectancy (den Boer, Oostendorp, Beems, Munneke, & Ev...…”
mentioning
confidence: 99%